Simultaneous Determination of Schisandrin and Promethazine with Its Metabolite in Rat Plasma by HPLC-MS/MS and Its Application to a Pharmacokinetic Study - Sijia Gao; Xuelin Zhou; Liwei Lang; Honghong Liu; Jianyu Li; Haotian Li; Shizhang Wei; Dan Wang; Zhuo Xu; Huadan Cai; Yanling Zhao; Wenjun Zou (International Journal of Analytical Chemistry)
This study aimed to develop a selective, simple, and sensitive HPLC-MS/MS method for the simultaneous determination of schisandrin and promethazine (PMZ) with its metabolite in rat plasma, which was further used for a pharmacokinetic herb-drug interaction study. HPLC-MS/MS analyses were performed on an Agilent Technologies 1290 LC and a 6410 triple quadrupole mass spectrometer. The following parameters, the lower limit of quantification (LLOQ), calibration curve, accuracy, precision, stability, matrix effect, and recovery, were validated. The linear range of the developed method for PMZ, its metabolite promethazine sulfoxide (PMZSO), and schisandrin in rat plasma was 0.5–200 ng/mL (R2 > 0.995), with an LLOQ of 0.5 ng/mL, which completely met the determination requirements of biosamples. The intra- and interday precision (RSD, %) was below 13.31% (below 16.67% for the LLOQ) in various plasma, whose accuracy (bias, %) was from −8.52% to 11.40%, which were both within an acceptable range. This method was successfully applied to a pharmacokinetic herb-drug interaction study after oral administration of PMZ with or without S. chinensis water extract. The results demonstrated that coadministration with the S. chinensis water extract might affect the pharmacokinetic behaviors of PMZ. In turn, when taken together with PMZ, the pharmacokinetic parameters of schisandrin, the main active component of S. chinensis, were also affected. The method established in the current study was selective, simple, sensitive, and widely available with good linearity, high accuracy and precision, and a stable sample preparation process. Moreover, this analytical method provides a significant approach for the investigation of herb-drug interaction between S. chinensis and PMZ. The potential pharmacokinetic herb-drug interaction of PMZ- and schisandrin-containing preparations should be noted.